Violence against young Australian women and association with reproductive events: a cross‐sectional analysis of a national population sample - Angela J. Taft; Lyndsey F. Watson; Christina Lee (Elsevier, 2004)
Abstract Objective:This study aimed to investigate associations between violence and younger women's reproductive events using Survey 1 (1996) data of the Younger cohort of the Australian Longitudinal Study of Women's Health (ALSWH). Methods:Multinomial regression, using composite variables for both violence and reproductive events, adjusting for socio‐economic variables and weighted for rural and remote areas. Results:23.8% of 14,784 women aged 18 to 23 years reported violence; 12.6% reported non‐partner violence in the previous year; and 11.2% reported ever having had a violent relationship with a partner. Of the latter group, 43% (4.8% overall) also reported violence in the past year. Compared with women reporting no violence, women reporting partner but not recent violence (OR 2.55, 95% CI 2.10-3.09) or partner and recent violence (OR 3.96, 95% CI 3.18-4.93) were significantly more likely to have had one or more pregnancies. Conversely, having had a pregnancy (2,561) was associated with an 80% increase in prevalence of any violence and a 230% increase in partner violence. Among women who had a pregnancy, having had a miscarriage or termination was associated with violence. Partner and recent violence is strongly associated with having had a miscarriage, whether alone (OR = 2.85, 95% CI 1.74-4.66), with a termination (OR = 4.60, 2.26-9.35), or with birth, miscarriage and a termination (OR = 4.12, 1.89-9.00). Conclusions and implications:Violence among young women of childbearing age is a factor for which doctors should be vigilant, well‐trained and supported to identify and manage effectively.